High-Resolution En Face Images of Microcystic Macular Edema in Patients with Autosomal Dominant Optic Atrophy. (28th November 2013) - Gocho, Kiyoko; Kikuchi, Sachiko; Kabuto, Takenori; Kameya, Shuhei; Shinoda, Kei; Mizota, Atsushi; Yamaki, Kunihiko; Takahashi, Hiroshi
Abstract : The purpose of this study was to investigate the characteristics of microcystic macular edema (MME) determined from the en face images obtained by an adaptive optics (AO) fundus camera in patients with autosomal dominant optic atrophy (ADOA) and to try to determine the mechanisms underlying the degeneration of the inner retinal cells and RNFL by using the advantage of AO. Six patients from 4 families with ADOA underwent detailed ophthalmic examinations including spectral domain optical coherence tomography (SD-OCT). Mutational screening of all coding and flanking intron sequences of the OPA1 gene was performed by DNA sequencing. SD-OCT showed a severe reduction in the retinal nerve fiber layer (RNFL) thickness in all patients. A new splicing defect and two new frameshift mutations with premature termination of the Opa1 protein were identified in three families. A reported nonsense mutation was identified in one family. SD-OCT of one patient showed MME in the inner nuclear layer (INL) of the retina. AO images showed microcysts in the en face images of the INL. Our data indicate that AO is a useful method to identify MME in neurodegenerative diseases and may also help determine the mechanisms underlying the degeneration of the inner retinal cells and RNFL.